ALFA-1-ANTITRYPSIN IS A PROGNOSTIC RISK OF DEVELOPING PREGNANCY-ASSOCIATED KIDNEY AND UTERINE DISEASES - Komarevtsev, V.M.; Balabanova, K.V.; Chernykh, Yu.A.; Karasev, I.E.; Haydash, I.S.; Haydash, I.A.; Komarevtseva, I.O. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the role of the biomarker of alpha-1-antitrypsinin the the development of pregnancy-associated renal cell carcinoma and pregnancy-associated uterine sarcoma within 1 years (56 weeks) and 35 years after childbirth. Our data proved the diagnostic value of determining the alpha-1-antitrypsin level for detecting cancer diseases, both in pregnant and non-pregnant women. Oncological diseases significantly increase the level of alpha-1-antitrypsin compared to all groups of healthy women. This is especially true for healthy pregnant women with preterm labor, where the increase in alpha-1-antitrypsin level in pathologies is 2.69 times. Using variation series of alpha-1-antitrypsin levels in blood serum of pregnant women with different periods of pregnancy, we created a prognostic risk model for the development of pregnancy-related cancer during the first year and during 35 years after preterm and timely birth, depending on the level of alpha-antitrypsin.
Keywords: alpha-1-antitrypsinin; pregnancy-associated renal cell carcinoma; pregnancy-associated uterine sarcoma